Postgraduate training in Social Work in the pandemic context: challenges of Emergency Remote Teaching - Silva, Maria Liduina de Oliveira e; Fernandes, Rafaela Bezerra; Tales Willyan (Argumentum, 2023)
This article deals with the postgraduate training process in Social Work in Brazil in the context of Emergency Remote Teaching (ERT), in the face of the covid-19 pandemic, whose scenario was a catalyst for the counter-reforms of education in the country that, under the aegis of the neoliberalism, finds in the Bolsonaro government the stage that sharpens and exposes the lack of commitment to public education. The reflections presented here, based on bibliographic research and data analysis, are derived from the information obtained through the mappings (2021 and 2022) of the impacts of the ERT in the area of ​​Social Work, carried out by the Association for Teaching and Brazilian Research in Social Work (Brazilian Association for Teaching and Research in Social Work ‎ —ABEPSS). The data make evident the challenges experienced in this context of exceptionality in the face of adherence to the ERT and point out the elements that need to be faced in the present time so that the damages of this teaching method do not remain as a deleterious legacy in the critical training process of the profession.